Repression of Diaminopimelate Decarboxylase by l-Lysine in Different Bacillus Species - Grandgenett, Duane P. (1971)
Synthesis of diaminopimelate decarboxylase in 7 of 11 different Bacillus species tested was subject to l-lysine repression.